Pembelajaran Proyek untuk Meningkatkan Kemampuan Kreativitas Kewirausahaan : Analisis Bibliometrik - Rika Purnama Sari (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This research aims to analyze bibliometric data using the supporting application Publish or Perish and mapping tools in VOSviewer with data in RIS format. The method used is descriptive quantitative to examine how Project-Based Learning can enhance creativity skills in entrepreneurship. From the search results, 200 journals were found from the years 2015-2024, which were then grouped into three categories based on their publication year. After categorizing the journal data, the most published articles were in 2022, indicating an opportunity for further research on the theme of entrepreneurial creativity. Entrepreneurial creativity can be possessed by students and can be developed through education. Entrepreneurship education is crucial to fostering creativity, innovation, and entrepreneurship, and provides information to those who wish to establish small-scale businesses. Entrepreneurship education can turn an individual into an entrepreneur and positively influence entrepreneurial attitudes and innovation. Entrepreneurship education not only imparts practical knowledge on how to start and manage a business but also plays a vital role in developing an entrepreneurial mindset, attitude, and skills such as perseverance, resilience to failure, and the desire to learn and grow. Project-based learning models can be used to enhance entrepreneurial motivation, as students not only understand the ideas but can also explain the importance of the knowledge and skills acquired.